1887 Wis. Sess. Laws 1308, ch. 409, § 36, pt. 53 - (:unkn) unknown (General Publisher, 1887)
Authorized the city to regulate and prohibit the concealed carry of any pistol, sling shot, knuckles of lead, brass, or other metal,, bowie knife, dirk, dagger, or any other dangerous or deadly weapon.
--
Keywords: CARRY - CONCEALED